In situ degradability of dry matter, crude protein and fiber of some feeds - Cabral, Luciano da Silva; Valadares Filho, Sebastião de Campos; Zervoudakis, Joanis Tilemahos; de Souza, Alexandre Lima; Detmann, Edenio (Pesquisa Agropecuaria Brasileira, 2005)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The objective of this work was to determine the kinetic parameters of the dry matter in situ degradation, crude protein and neutral detergent fiber for corn silage, elephant-grass silage, Tifton-85 grass hay and soybean meal. Three rumen canulated cattle were used, with mean liveweight of 400 kg. Feeds were weighted in naylon bags, and incubated in the rumen at once. Roughages were removed at 0, 2, 4, 8, 16, 24, 48 and 72 hours, and soybean meal at 0, 2, 4, 8, 16, 24 and 48 hours after incubation. Residues in the bags were analyzed for dry matter, crude protein and neutral detergent fiber. Dry matter and crude protein of soybean meal presented highly degradable potential, as well as crude protein of corn silage. Tifton-85 grass hay presented high indigestible neutral detergent fiber fraction and therefore, low potential dry matter degradation. Amount of the neutral detergent fiber and its kinetic characteristic has a marked effect on digestion of feeds.